Is the body composition development in premature infants associated with a distinctive nuclear magnetic resonance metabolomic profiling of urine?. (18th July 2019) - Morniroli, Daniela; Dessì, Angelica; Giannì, Maria Lorella; Roggero, Paola; Noto, Antonio; Atzori, Luigi; Lussu, Milena; Fanos, Vassilios; Mosca, Fabio
Abstract: Objective: Preterm infants' body composition at term-corrected age differs from that of term infants but appears to be similar at the age of 3 months. The aim of this study was to compare the metabolomic pattern of preterm infants at term and at 3 months with that of term infants and to determine its association with body composition development. Method: We designed a pilot study. Growth and body composition were evaluated by an air displacement plethysmography system in 13 preterm infants and seven term newborns at term and at 3 months of corrected age. Urine samples were collected at the same time points and analysed by nuclear magnetic resonance. Results: At term-corrected age, preterm infants showed a higher fat mass percentage compared with that of term newborns, whereas at 3 months of corrected age, the body composition parameters were similar between the groups. At the first time point, nuclear magnetic resonance analysis showed a urinary increase in choline/phosphocholine, betaine and glucose in preterm infants. At the second time point, the preterm group exhibited a urinary increase in choline/phosphocholine and a decrease in betaine. Conclusions: The increased urinary excretion of choline, a betaine precursor, could reflect a potential altered metabolism in preterm infants.